2018
DOI: 10.1136/bcr-2017-222384
|View full text |Cite
|
Sign up to set email alerts
|

Rothmund-Thomson syndrome (RTS) with osteosarcoma due toRECQL4mutation

Abstract: Rothmund-Thomson syndrome (RTS) is a rare autosomal recessive disorder with clinical features consisting of poikiloderma, skeletal abnormalities, sparse hair, absent or scanty eyelashes and eyebrows and short stature. Patients with RTS due to genetic mutations of genes carry a high risk of developing osteosarcoma during childhood. Because of this, early genetic diagnosis is important. Here, we describe a 14-year-old white boy who developed an erythematous rash on both cheeks before the age of 3 months and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Table S1 provides a general overview of the RECQL4 pathogenic variants detected to our knowledge in 35 patients who developed cancer presenting with all the three RECQL4 -associated diseases (28 RTS, 6 RAPADILINO and 1 BGS patients) [ 8 , 26 , 27 , 28 , 30 , 32 , 33 , 34 ]. Out of 35 RECQL4 -mutated patients, 34 carried at least one pathogenic variant affecting the helicase domain, confirming the association between deleterious mutations in the RECQL4 gene and cancer predisposition first assessed by Wang in 2003 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table S1 provides a general overview of the RECQL4 pathogenic variants detected to our knowledge in 35 patients who developed cancer presenting with all the three RECQL4 -associated diseases (28 RTS, 6 RAPADILINO and 1 BGS patients) [ 8 , 26 , 27 , 28 , 30 , 32 , 33 , 34 ]. Out of 35 RECQL4 -mutated patients, 34 carried at least one pathogenic variant affecting the helicase domain, confirming the association between deleterious mutations in the RECQL4 gene and cancer predisposition first assessed by Wang in 2003 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies indicated that they used non-NGS methods (Sanger, Direct sequencing, SNP-array, Multiplex ligation-dependent probe amplification) and were therefore limited in the number of genes and CH variants analyzed (Quesnel et al, 1999;De Rosa et al, 2000;Østergaard et al, 2005;Okkels et al, 2006;Scott et al, 2007;Herkert et al, 2011;Leenen et al, 2011;Chmara et al, 2013;Bakry et al, 2014;Piane et al, 2016;Svojgr et al, 2016;Moriyama et al, 2017;Sharapova et al, 2018). Three clinical/case report studies did not describe the exact DNA sequencing technology used (Peters et al, 2009;Majumdar et al, 2010;Salih et al, 2018); however, we inferred that Sanger sequencing was inferred in these three studies because single genes were the focus of the studies, parent DNA was also sequenced, and DNA variant locations were provided by the authors. Across all studies, the methodology used to estimate haplotypes varied considerably ( Table 3 and Supplementary Data 1:T1).…”
Section: Methodologies Used To Identify Ch Variants and Assess Pathogmentioning
confidence: 99%
“…One study used evidence from RNA-seq data that the alternate alleles were on different chromosomes (Zhang et al, 2015). All other studies that performed phasing used sequence data from the patient and his/her parent(s) (i.e., Mendelian inheritance; Quesnel et al, 1999;De Rosa et al, 2000;Okkels et al, 2006;Scott et al, 2007;Peters et al, 2009;Majumdar et al, 2010;Herkert et al, 2011;Leenen et al, 2011;Chmara et al, 2013;Bakry et al, 2014;Valentine et al, 2014;Spinella et al, 2015;Piane et al, 2016;Svojgr et al, 2016;Diets et al, 2018;Diness et al, 2018;Salih et al, 2018;Sharapova et al, 2018;Zhang et al, 2018;Maciaszek et al, 2019;Schieffer et al, 2019).…”
Section: Methodologies Used To Identify Ch Variants and Assess Pathogmentioning
confidence: 99%
See 2 more Smart Citations